The Acceptability, Feasibility, and Effectiveness of Breast Massage Combined with Acupoint Stimulation to Promote the Volume of Human Milk in Mothers with Preterm Infants: A Pilot Study. (25th February 2021) - Sheng, Jia; Ding, Yan; Wang, Jing; Zhang, Junping; Qi, Xingling; Xia, Haiou
Abstract : Background . Preterm infant mothers have always encountered difficulties in human milk production. For this reason, an intervention of breast massage combined with acupoint stimulation was designed to increase the production. Purpose . Through a pilot randomized trial, we assessed the acceptability, feasibility, and effectiveness of breast massage combined with acupoint stimulation and the study procedures. Methods . 40 participants of preterm infants born at less than 34 weeks of gestation were randomly allocated to the CG (control group) or the EG (group with breast massage combined with acupoint stimulation). Data related to the acceptability, feasibility, and effectiveness of the intervention and research procedures were collected and analysed. Results . The daily volume progressively increased each day in the first 7 days in both groups and a significant difference was observed between the groups (P < 0.001). The initiation time of lactogenesis stage II was 50.06 ± 6.78 (40.00–64.00) hours in the EG and 66.18 ± 14.64 (48.00–96.00) hours in the CG, where a significant difference was detected (P < 0.05). The mean score of satisfaction with the intervention in the EG was 4.56 ± 0.32 (4.0–5.0), while the retention rates were 82.5% and 85.5% (17/20) in the CG, and 80% (16/20) in the EG. Conclusion . This pilot study was oriented towards the effectiveness of breast massage combined with acupuncture stimulation for the increase of human milk production in the participants. The intervention was accepted well and the study process was reasonable. A large-scale RCT will be able to determine the beneficial effects of this intervention on human milk production.